Hubungan Frekuensi Pemberian Konsultasi Gizi dengan Kepatuhan Diit Serta Kadar Gula Darah Penderita Diabetes Mellitus Tipe II Rawat Jalan di RS Tugurejo Semarang - Eva Mona; Sufiati Bintanah; Rahayu Astuti (Universitas Muhammadiyah Semarang, 2012)
Diabetes mellitus is a collection of symptoms that occur in a person caused by an increase in blood glucose levels due to insulin deficiency both absolute and relative terms (Soegondo, 2007). The purpose of this study to know frequencies relations consultancy with compliance diit nutrition and blood sugar levels of people with Diabetes Mellitus Type IITugurejo Hospital in Semarang.This research is in the field of clinical nutrition with cross sectional approach is presented by means of descriptive and analytical. The study population was all patients with Diabetes Mellitus Type II Outpatient in Hospital Tugurejo Semarang Outpatient July 2012. Samples were taken from a total population of some 34 people who met the inclusion criteria.Types of data collected is primary and secondary.The results showed that the characteristics of the sample by sex most women (73.5%), the largest age 50-59 years (44.1%), highest education level SMA / SMK (38.2%), most work housewife (70.6%), normal nutritional status (41.2%), the frequency of nutritional consultation 2 - 4x (50.0%), adherence diit quite adherent (61.8%), and blood glucose> 200mg / dl (73.5%). Analysis of the data using the Spearman Rank Correlation test showed no association with the frequency of nutritional consultation diit compliance with r = 0.346 and p-value of 0.045 (<0.05) and no relationship diit compliance with blood glucose levels with r= 0.537 and p-value 0.001 (<0.05).Keywords : blood glucose levels, diabetes mellitus, diit compliance